The Power of Belief: Unpacking Religion's Role in Mental Health Outcomes - Napilah, Paridah; Truna, Dody S.; Albustomi, Ahmad Gibson (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2024)
Every human being has experienced various problems in his life, so it has an impact on his mental health. The purpose of this paper is to look at the extent of the influence of religion on mental health. This paper uses a literature study by looking for information both from books and journals and the latest research related to the theme of discussion. The main sources used in this study are books about God in the human brain. The results of this research show that religion can have an influence on mental health. This is because there is an attitude of surrender to the Most High, namely God. This attitude of surrender causes optimism towards a person so that various positive feelings such as happiness, pleasure, and calm arise when facing various life problems. Contribution: By synthesizing information from multiple sources about religion's impact on mental health, the article contributes to ongoing discussions in both academic and clinical settings about how best to support individuals facing psychological difficulties through their faith.